High-Yield Bond Default and Call Risks - McDonald, Cynthia G.; Gucht, Linda M. Van de (The Review of Economics and Statistics, 1999)
This paper empirically investigates high-yield bond default and call behavior using a competing risks hazard model that simultaneously estimates the impact of bond age, issue-specific characteristics and business conditions on both events. Results reveal nonmonotonic aging effects: default rates increase and then drop while call rates first increase and then level off. Rating and coupon size affect default risk, while maturity and issue size impact only call rates. Defaults are more likely when economic conditions have worsened and no improvement is anticipated. Calls are more likely when interest rates have decreased but are expected to rise.